Food Security in Algeria under Wheat Import Dependence: The Role of Supplier Diversification, 2010–2026 - Salah OUYABA (Journal of Excellence for Economics and Management Research, 2026)
This paper examines whether selective import substitution can strengthen food security in Algeria under persistent dependence on cereal and wheat imports. Using a descriptive-analytical case study approach and secondary data from FAO, USDA, OEC, WITS, official reports, and recent literature for 2010–2026, the study measures import dependence and evaluates the roles of domestic production, strategic stocks, and supplier diversification.The results show that wheat consumption increased from 8.75 million tons in 2010/11 to 11.95 million tons in 2025/26, while the wheat import dependence ratio remained high, ranging from 63.1% to 80.9%. Although domestic output improved in some seasons, cereal import requirements remained around 14.0–14.6 million tons in the most recent years. The supplier structure became less concentrated, with the share of the top three wheat suppliers falling from 94.0% in 2018 to 60.3% in 2024, while strategic storage capacity expanded. These developments improved supply resilience but did not produce a structural decline in external dependence. The paper concludes that food security in Algeria cannot rely on production expansion alone and that an effective import substitution strategy should combine productivity gains, storage capacity, logistics, and supplier diversification.